Study and Design of Compressed Air System for Optimum Operation - Muhammad Farid Bin Abdullah, Muhammad Farid (Universiti Teknologi PETRONAS, 2008)
This is a report on the study and design of compressed air system installed at a plant for manufacturing processes. The plant suffers high electrical energy consumption after modifications were done to increase the production capacity of the original system. This provides an opportunity to study the reasons for such situation. The project will study both the original and modified systems and compare the performances of the systems. Consequently a new optimized system will be designed. The project is divided into two phases namely phase 1 and phase 2. The first phase focuses on the study of the original and modified systems and the second phase will be on design of a new system. The second phase involves design of the compressed air system by matching supply to demand of compressed air. Phase one study is performed by evaluating parameter that affects the usage of the air compressor which is pressure drop. The findings indicated that pressure drops were mainly contributed by pipe friction and losses due to pipe fittings. However other reasons which contributed significantly to pressure drop was high velocity flow in small diameter pipe, mainly in 15mm diameter pipe. Analysis result showed that the flow velocity in 15mm diameter pipe increased by 13 times the flow velocity in the mainline. Thus higher flow velocity increased the pressure drops greatly when the changes in all other parameters were relatively small. Other sources of pressure drops was also identified as leakage at the connection of piping and flexible hoses. Phase 2 requires evaluation of design parameters required to ensure efficient operation. The design parameters are unique to each system therefore each compressed air system has to be evaluated exclusively. Demand of compressed air is calculated by summing of required volumetric flowrate during operation of the plant and this is matched by designing supply system which able to deliver the required flowrate. At the end of the report, recommendations are given to optimize the system.